Territoriality, breeding philopatry, and nest site selection of Chestnut Seedeater ( Sporophila cinnamomea ) in grasslands of southern Brazil - Jonas Rafael Rodrigues Rosoni; Caio J. Carlos; Carla Suertegaray Fontana (Journal of Field Ornithology, 2024)
We provide the first insights on the territorial behavior of the Chestnut Seedeater ( Sporophila cinnamomea ), a vulnerable, migratory species inhabiting the Pampas grasslands of South America. Our study aims to describe and estimate territory size, calculate rates of philopatry and breeding dispersal, describe the main aspects of the species’ territorial behavior, and characterize nest sites. Over four breeding seasons (2018–2022), we monitored 70 adult individuals across two grassland areas of southern Brazil. We applied the Kernel Density Estimation method to estimate the territory size and core areas and analyzed the composition and floristic structure of nest sites. The average size of breeding territories was 1.91 ± 0.59 ha, and the core areas were 0.23 ± 0.05 ha. Remarkably, the average size of territories of philopatric males did not significantly vary in consecutive breeding seasons. The breeding philopatry rate was 51.5%. Moreover, we observed no significant differences in dispersion distance among consecutive breeding seasons, suggesting stable breeding site fidelity. Analysis of nest sites identified 14 plant species exhibiting higher abundance, with dense and tall vegetation prevalent. These findings underscore the importance of understanding population dynamics and the composition and structure of vegetation within Chestnut Seedeater nest sites as initial steps toward developing effective management and conservation strategies for their habitats.